Design of Low-Loss Coaxial Cavity Bandpass Filter with Post-Manufacturing Tuning Capabilities - Zakaria, Zahriladha; Sam, Weng Yik; Abd Aziz, Mohamad Zoinol Abidin; Meor said, Maizatul Alice (2012)
This paper presents a low-loss of coaxial cavity bandpass filter with post-manufacturing tuning capabilities.A systematic filter development using the lowpass prototype as a starting point to produce 4th degreeChebyshevbandpass response is demonstrated. The coaxial cavity filter based upon TEM mode of propagation has the center frequency of 2.5 GHz and bandwidth of 168MHz. The insertion loss of 0.15 dB insertion loss and return loss better than 15 dB areobtained particularly in the passband. This type of microwave filter would be useful in any microwave systems where the low insertion loss and high selectivity are crucial, such as in a base station, radar and satellite transceivers.